Is school curriculum still relevant in digital culture? Debates and challenges on contemporary cultural authority - Dussel, Inés (Education Policy Analysis Archives, 2014)
School curriculum has been under heavy attack for some decades now, either from the critical positions in the field of curriculum theory itself or from wider political and cultural movements. The article starts considering an operational definition of the curriculum of modern schooling as a public document that expresses, in a pedagogical language, a synthesis of a cultural ideal about how and who defines cultural authority in a given society. Thus, it is inextricably bounded to the production of a cultural authority and a given power-knowledge regime. My argument seeks to analyze the historic configuration of some of its basic traits, and also trace contemporary challenges to its authority. It deals specifically with the changes and polemics brought by digital culture, which question the centralization of the curriculum and propose instead alternative hierarchies and organization for knowledge based on popularity and consumers’ tastes as well as different ways of knowing, more emotional and immediate. The analytical approach is informed by Foucaultian studies, the political sociology of curriculum, Actor-Network Theory, and historical and cultural studies on media and digital technologies. I argue that the curriculum still holds relevance as a public document that seeks to organize educational experiences in schools, and that the negotiations and translations that are taking place between school curriculum and digital technologies should not be lightly dispatched as they point to the complex debates and challenges that have structured the curriculum of modern schooling.